Determination of arsenic and cadmium uptake by rice from topsoil - Desheng Yang; Zhechuan Liu; Wenqi Zhao; Ting Du; Shengyang Fan; Zhuang Xiong; Shaobing Peng; Xiaoxiao Li; Fei Wang (Modern Agriculture)
Abstract Topsoil is the main sink of various pollutants and the direct source of heavy metal uptake by crops. In a 2‐year field experiment conducted in central China from 2016 to 2017, the significant role of topsoil in pollutant absorption, in particular the arsenic (As) and cadmium (Cd) uptake in rice was examined quantitatively. Two soil treatments, removing half of the topsoil (TR) and a control (CK), were applied alongside two rice varieties ‐ Huanghuazhan (HHZ, indica inbred) and Yangliangyou6 (YLY6, indica hybrid). On average, TR reduced the As and Cd concentrations in grain by 10.0% and 56.2%, respectively. The reduction was linked to lower pollutant concentrations in soil above the hardpan and rice straw. TR also decreased shoot As and Cd accumulation by 30.7% and 67.8% at maturity, with topsoil at 12–15 cm depth contributing an average of 2372 μg As m−2 (30.1%) and 138 μg Cd m−2 (66.1%) to total uptake of As and Cd, respectively. Contribution of topsoil to total As uptake remained consistent across growing stages, while for Cd, topsoil contributed 24.8% before heading and 81.2% after. Moreover, varietal differences were observed, with TR significantly reducing grain As and Cd concentrations of YLY6 but no difference in HHZ. This study quantifies topsoil's impact on As and Cd uptake in rice, and underscores genotypic variations in their response to topsoil removal.